CONTENT of VOLUME 19 ISSUE 2 DECEMBER 2023 (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
THE IMPACT OF STUNTING MALNUTRITION OF ORODENTAL HEALTH IN CHILDREN: A SCOOPING REVIEWI Gusti Ayu Ari Agung, Dewa Made Wedagama, I Gusti Ayu Agung Hartini, Ni Putu Widani Astuti, I Nyoman Panji Triadnya Palgunadi, Gusti Ayu Yohanna Lily, Ni Putu Idaryati, Ilma Yudistian74-79 PERIODONTICS IN ARTIFICIAL INTELLIGENCE ERA : A LITERATURE REVIEWNi Wayan Arni Sardi, Ni Luh Putu Sri Maryuni Adnyasari, Made Talitha Suryaningsih Pinati80-85 REGENERATIVE TREATMENT USING PERIODONTAL FLAP SURGERY COMBINED Ti-OSS®, PERICARDIUM MEMBRANE AND PLATELET-RICH FIBRIN IN CHRONIC PERIODONTITISAbyan Teguh Saputro, Vincensia Maria Karina86-93 MINIMAL INVASIVE FOR MAXIMAL RECOVERY IN DENTAL TRAUMA : A CASE REPORTAnak Agung Manik Swayoga, Ilma Yudistian94-100 AESTHETIC IMPROVEMENT IN ONE VISIT PERIODONTAL PLASTIC SURGERY USING SCALPEL AND LASER SURGICAL TECHNIQUE (CASE REPORT)Nabilah, Vincensia Marina Karina101-108 TELEDENTISTRY IN A JURIDICAL PERSPECTIVE: CRIMINAL, CIVIL AND ADMINISTRATIVE ASPECTSNyoman Ayu Anggayanti, Ida Bagus Fajar Manuaba, I Gusti Agung Gede Utara Hartawan109-114 THE EFFECTIVENESS OF ORANGE PEEL EXTRACT TOOTHPASTE IN LIGHTENING TEETH AND PREVENTING BACTERIAL INFECTIONS LEADS TO HALITOSISDentino Asmara Putra, Ni Nengah Aderinaarta Pramudani, Armyawati, Wiwekowati115-120 CASE MANAGEMENT OF ANTERIOR TOOTH INTRUSION DUE TO TRAUMAAryo Sutowijoyo, Prima Nerito121-126 TRAINING OF TRAINERS METHOD FOR ELEMENTARY SCHOOL TEACHERS TO IMPROVE DENTAL HEALTH KNOWLEDGEYudha Rahina, I Gusti Agung Ayu Chandra Iswari Dewi, I Gusti Ayu Ratih Pramesti, Pudak Elang, Eko Sri Yuni Astuti127-131 FRENECTOMY ON MAXILLARY LABIAL FRENULUM PENETRATING PAPILLA TYPE BY CONVENTIONAL SURGICAL TECHNIQUES: A CASE REPORTDwis Syahriel, Dwis Syahrul, Arya Kusuma Agraha, Asri Riany Putri132-138 COST BENEFIT ANALYSIS OF OPENING DENTAL POLY SERVICES OR CHILDREN'S PHYSIOTHERAPY POLY SERVICES AT SAFAKILLAH CLINICPrima Nerito, Aryo Sutowijoyo139-147 NECROSIS FACTOR-ALPHA A POTENTIAL THERAPEUTIC TARGET FOR PERIODONTITIS AND DIABETES MELLITUSAngela Widjaja, Ahmad Syaify, Hendrawati148-157 THE EFFECTIVENESS OF CEMCEM (Spondiaspinnata (L.f) Kurz) LEAF EXTRACT IN INHIBITING THE GROWTH OF Streptococcus mutansPutu Sulistiawati Dewi, I Made Merta Suparka158-163 IDENTIFICATION AND TREATMENT OF ERYTHEMA MULTIFORME INDUCED BY ALLOPURINOLI Nyoman Gede Juwita Putra, Raziv Ganesha, I Gusti Ngurah Putra Dermawan164-169 ACUTE TOXICITY TEST OF AMBON BANANA TREE SAP EXTRACT ON MICE (Mus Muculus L.)Setiawan, Hendri Poernomo, Reza Pramana170-176 KNOWLEDGE LEVEL OF DENTAL STUDENTS FKG UNBRAH ABOUT THE TREATMENT OF STAINLESS-STEEL CROWN (SSC) IN PEDIATRIC PATIENTS AT DENTAL HOSPITAL BAITURRAHMAHSri Pandu Pandu, Leny Sang Surya, Utami Arma, Resa Ferdina, Hanifah Maharani Al Asad177-181 IMPLEMENTATION OF THE MOBILE-BASED DENTALK APPLICATION AS A MEDIA FOR INCREASING PUBLIC KNOWLEDGE IN USING THE TELEDENTISTRY APPLICATIONSari Aldilawati, Amanah Pertiwisari, Andi Muhammad Irfan M.Amir182-186 ANTIBACTERIAL COMPARISON BETWEEN MANUKA HONEY AND TUALANG HONEY AGAINST PORPHYROMONAS GINGIVALIS BACTERIA.Veronica Septnina Primasari, Desy Fidyawati, Ike Nurmalisari Ramadhani187-194 EFFECT OF KECEMCEM TREE (SPONDIAS PINNATA) BARK EXTRACT GEL TO INCREASE COLLAGEN POST WISTAR RATS CURETTAGEEka Pramudita Ramadhany, Media Sukmalia Adibah, Astrid Rahayu Dewi195-201 THE RELATIONSHIP BETWEEN STRESS DURING THE COVID-19 PANDEMIC AND THE INCIDENCE OF RECURRENT APHTHOUS STOMATITISAfryla Femilian, Khulia Furaida, Afina Hasnasari Heningtyas202-208 SPACE SEARCH FOR MINOR CROWDING CASES WITH EXPANSION PLATE IN PATIENTS WITH A HISTORY OF ANTIDEPRESSANT DRUG CONSUMPTIONPuspitarini Nindya Wardana, Yely Okta Mariza209-215 THE ROLE OF TRICHOMONAS TENAX IN PERIODONTAL DISEASE: A LITERATURE REVIEWNadia Nabiilah Rahmah Rayugi, Emma Rachmawati, Ina Hendiani216-221 DESCRIPTION OF PATIENTS WITH ODONTECTOMY IN RSUD SULTAN FATAH DEMAKFuad Fatkhurrohman, Syarifah Nova Amiza Zam, Dea Hardyana Putri, Khairunnisa Pulungan, Isnadia Rachmah Ika222-227 THE RELATIONSHIP OF CHEWING GUM WITH TEMPOROMANDIBULAR JOINT DISORDERS: RAPID REVIEWEvy Carolina Choandra, Rasmi Rikmasari, Seto Pramudita228-236 INHIBITORY POWER OF MAS BANANA PEEL EXTRACT (MUSA ACUMINATA LADY FINGER) ON THE GROWTH OF STAPHYLOCOCCUS AUREUS IN VITRODwis Syahrul, Ni Putu Widani Astuti, Dwis Syahriel, Desak Putu Diah Pradnyani, M. Dian Firdausy237-241